The Covid-19 pandemic and the new poor in Africa: The straw that broke the Camel's back - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study assesses the incidence of the Covid-19 pandemic on poverty levels in 50 African countries by employing the PovcalNet computational tool for poverty monitoring. The empirical evidence is based on: (i) Pre Covid-19 macroeconomic projections of October 2019 and revised macroeconomic projections of April 2020 and (ii) three poverty thresholds, notably, US1.90, US3.20, and US5.50 per day for the extreme, middle and higher poverty lines. The following main findings are established. First, the extreme poverty line of US1.90 per day has increased by US0.1 per day while the middle poverty line and the higher line have increased by US0.19 and US0.32, respectively. Second, the poverty headcount has increased to 35.85% for the US1.90 poverty line, 57.55% for the US3.20 per day poverty line and 76.42% for the higher poverty line (US5.5 per day). Third, the corresponding additional percentage points in poverty headcount ratio are: (i) an increase of 2.09% for the poverty thresholds of US1.90 per day and US3.2 per day, corresponding to 28, 140, 345 and 26, 418, 200 million, respectively of the new poor in absolute terms and (ii) a boost of 1.78% for the higher poverty line of US5.5 per day, corresponding to 19, 062, 643 million of the new poor. Fourth, country-specific tendencies are also provided for more targeted policy implications.
Keywords: H12; I12; I30; O55; 330; Coronavirus; pandemic; poverty; Africa; sustainable development